Incidencia del nivel de competición en el rendimiento del bloqueo en voleibol femenino - Murillo, B.; Julian, J. A.; Garcia-Gonzalez, L.; Abarca-Sos, A.; Zaragoza, J. (Revista Internacional de Ciencias del Deporte, 2014)
In this work we have observed, analyzed and assessed the blocking action game in women's volleyball, for a description of the technical-tactical gesture according to the level of competition. To do this we used a mixed observation tool consists of a system of field formats (each criterion consists of a system of categories E / ME) that values the context of play, the tactical situation, the technical and the result of action. 1645 were blocking actions from three different levels of competition. Descriptive analyzes were made of generalisability and variability, with the aim to determine the models that best explain significant variability in blocking performance, and assessing the variance associated with each of the categories, taking into account their interactions. Having found a larger complexity on the models of execution of the blocking technique the higher the level of competition is.